Widmo liberalizmu - Klejdysz, Natalia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The notion of ‘liberalism’ is beginning to acquire a new meaning in Polish political discourse. This ‘new liberalism’ is actually a distortion of liberal thinking and does not have much in common with proper liberalism. It has become a demon that politicians with anti-liberal attitudes use to frighten their potential voters. The reason for that is that their political opponents are associated with liberalism. Therefore, the author attempts to identify liberalism and the directions of its evolution in order to emphasize the fact that the fundamental values of liberalism do not actually correspond to the anti-liberal claims employed in political disputes.